Meta-analysis of the effects of n-3 polyunsaturated fatty acids on haematological and thrombogenic factors in type 2 diabetes - Hartweg, J; Farmer, A; Holman, R; Neil, H (Springer, 2007)
Aim/hypothesis: To determine whether marine-derived n-3 polyunsaturated fatty acids (n-3 PUFA) (also known as omega-3 fatty acids) have beneficial effects on haematological and thrombogenic risk markers in addition to dyslipidaemia, in patients with type 2 diabetes. Methods: A systematic review and meta-analysis of randomised controlled trials compary dietary or non-dietary intake of n-3 PUFA with placebo in type 2 diabetes was conducted by systematically searching databases from 1966 to February 2006. Changes in C-reactive protein, IL-6, TNF-α, platelet function, fibrinogen, factor VII, von Willebrand factor, endothelial function, heart rate and blood pressure were recorded. Inclusion of studies, data extraction and quality were assessed independently in duplicate. Results: Tweleve trials involving 847 subjects with a mean treatment duration of 8.5 weeks included sufficient data to permit pooling. Cpmpared with placebo, n-3 PUFA supplementation had a significant effect on two outcomes: reducing the level of diastolic blood pressure (five trials, 248 subjects) by a mean of 1.8 mm Hg (95% CI 0.0-3.6, p=0.05) and increasing factor VII (two trials, 116 subjects) by 24% (95% CI 7.2-42.6, p=0.006). There were no significant effects on systolic blood pressure, fibrinogen or heart rate. Conclusions/interpretation: These results suggest that, in addition to the recognised effects on dyslipidaemia, n-3 PUFA decreases diastolic blood pressure, and appears to increase factor VII. Larger and more rigorously conducted clinical trials are required to establish conclusively the role of n-3 PUFA in cardiovascular risk markers and clinical outcomes in type 2 diabetes.